ANALISIS PELAKSANAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN PADA KOTA TOMOHON - Lengkong, Yesika Claudia; Nangoi, Grace B.; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This scientist was done at the office of the city’s government of Tomohon was especially done with Regional Financial (Income, Financial, and Regional Assets) the city of Tomohon located in the North Sulawesi Province. While the implementation time of this research is from April 2018 to September 2018. The purpose of this study was to determine the implementation of registration, data collection, assessment, determination, payment, service, collection and supervision in PBB-P2 collection by the Office of Revenue, Management of Finance and Regional Property in Tomohon. The population in this study are several individuals who are the source of data collection. The research sample is the Tomohon City Regional Revenue Service Officer who deals with Regional Taxes and Levies. In this study, the author uses descriptive methods. Data collection techniques used in this study are Field Research and Library Research. Data analysis was carried out by presenting the results obtained from research conducted to study and discuss the management of Land Taxes and Rural and Urban Buildings at the Tomohon City Regional Revenue Service. The conclusions of this study are: The implementation of PBB-P2 in the Department of Revenue, Management of Finance and Regional Property in Tomohon has followed the existing rules procedures and is in accordance with UN legislation, namely Law No. 12 of 2009 concerning Land and Building Taxes.Keywords :Tax assessments of the earth and the country and urban buildings